Seasonal Variation of Antiretroviral Drug Exposure during the Year: The Experience of 10 Years of Therapeutic Drug Monitoring - Jessica Cusato; Jacopo Mula; Alice Palermiti; Alessandra Manca; Miriam Antonucci; Valeria Avataneo; Elisa Delia De Vivo; Alice Ianniello; Andrea Calcagno; Giovanni Di Perri; Amedeo De Nicolò; Antonio D’Avolio (Biomedicines, 2021)
Although studies show an annual trend for immunosuppressive drugs, particularly during different seasons, no data are available for antiretroviral drugs exposures in different periods of the year. For this reason, the aim of this study was to investigate an association between seasonality and antiretroviral drugs plasma concentrations. Antiretroviral drugs exposures were measured with liquid chromatography validated methods. A total of 4148 human samples were analysed. Lopinavir, etravirine and maraviroc levels showed seasonal fluctuation. In detail, maraviroc and etravirine concentrations decreased further in summer than in winter. In contrast, lopinavir concentrations had an opposite trend, increasing more in summer than in winter. The etravirine efficacy cut-off value of 300 ng/mL seems to be affected by seasonality: 77.1% and 22.9% of samples achieved this therapeutic target, respectively, in winter and summer, whereas 30% in winter and 70% in summer did not reach this value. Finally, age over 50 years and summer remained in the final multivariate regression model as predictors of the etravirine efficacy cut-off. This study highlights the seasonal variation in antiretroviral drugs plasma concentrations during the year, leading to a better understanding of inter-individual variability in drug exposures. Studies are required in order to confirm these data, clarifying which aspects may be involved.